2017
DOI: 10.1515/mmcks-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Trademark dilution: comparing the effects of blurring and tarnishment cases over brand equity

Abstract: Abstract. Trademark dilution is, in a general sense, a reduction in brand equity due to the unauthorized use of the trademark by third parties (junior brands)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This does not mean associations are not important; they have a positive effect over intentions at lower levels of awareness (recall or recognition). Studies in different contexts have shown that better associations positively influence the perceived value of the brand (or brand equity) (Buil et al , 2013; Yoo et al , 2000; Macias and Cerviño, 2019), which, in turn, has a positive effect on intentions (Buil et al , 2013; Yoo and Donthu, 2001) and desired behaviors (Macias and Cerviño, 2017). The present study represents a step forward contributing with evidence for agricultural supplies and services brands, showing a moderating and unexpected role of awareness that was consistent in two different samples.…”
Section: Discussionmentioning
confidence: 99%
“…This does not mean associations are not important; they have a positive effect over intentions at lower levels of awareness (recall or recognition). Studies in different contexts have shown that better associations positively influence the perceived value of the brand (or brand equity) (Buil et al , 2013; Yoo et al , 2000; Macias and Cerviño, 2019), which, in turn, has a positive effect on intentions (Buil et al , 2013; Yoo and Donthu, 2001) and desired behaviors (Macias and Cerviño, 2017). The present study represents a step forward contributing with evidence for agricultural supplies and services brands, showing a moderating and unexpected role of awareness that was consistent in two different samples.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, possible negative effects of dilution by third party LPs should be considered (e.g. Macías and Cerviño, 2017).…”
Section: Introductionmentioning
confidence: 99%